Ag-doped InP/ZnS quantum dots for type-I photosensitizers. Issue 16 (7th February 2023) - Ren, Can; Hu, Die; Cui, Yanyan; Chen, Peixian; Xu, Xiaoqian; Cheng, Jiaji; He, Tingchao
Abstract : Ag-doping can efficiently enhance the multiphoton absorption and type-I photodynamic therapy efficiency of InP-based quantum dots. Abstract : Water-soluble Ag-doped InP/ZnS quantum dots (QDs) with high photoluminescence quantum yield were synthesized and characterized. Their maximum two- and three-photon absorption cross sections are determined as ∼1.7 × 10 4 GM at 820 nm and ∼1.7 × 10 −76 cm 6 s 2 photon −2 at 1260 nm. Importantly, for the first time, we demonstrated that Ag-doped InP/ZnS QDs can be used for type-I photodynamic therapy and are more suitable for the hypoxic environment of tumors.